ANALISIS PENINGKATAN KUALITAS BUIS BETON DALAM UPAYA ELIMINASI LOSSES MENGGUNAKAN METODE SIX SIGMA DAN FMEA PADA UD. MARJOKO BETON - Sriwidodo, Dwi; Khasanah, Rahayu; Sodikin, Imam (Jurnal Rekavasi, 2023)
The production process is said to be good when it produces products that are in accordance with the standards set by the company without any product defects. The company uses the six sigma method as a quality control tool to reduce product defects by implementing the Define, Measure, Analyze, Improve, Control (DMAIC) steps. Six Big Losses and FMEA to analyze the dominant factors that cause defective products and identify defects in concrete buis. This study aims to find out which companies implement quality control using the Six Sigma method. Based on the Six Big Losses analysis, the highest losses were process defect losses of 57.84% and equipment failures of 32.38%. There are 6 critical wastes out of a total of 13 wastes with the highest RPN value, which is caused by a human error of 180. The Sigma value is 3.06 or still within the control limits. Following are some recommendations for improvement that can be given to the company: carry out quality control at each stage of the production process, evaluate the workforce, contract with suppliers of prime quality materials, provide adequate raw material warehouses